Health care informatics. - Siau, K. (IEEE Transactions on information technology in biomedicine)
The health care industry is currently experiencing a fundamental change. Health care organizations are reorganizing their processes to reduce costs, be more competitive, and provide better and more personalized customer care. This new business strategy requires health care organizations to implement new technologies, such as Internet applications, enterprise systems, and mobile technologies in order to achieve their desired business changes. This article offers a conceptual model for implementing new information systems, integrating internal data, and linking suppliers and patients.